Woman's right to preach the gospel. A sermon, preached at the ordination of the Rev. Miss Antoinette L. Brown, at South Butler, Wayne county, N.Y., Sept. 15, 1853 ... - Lee, Luther, 1800-1889.; Stone, Lucy, 1818-1893; Susan B. Anthony Collection (Library of Congress); National American Woman Suffrage Association Collection (Library of Congress) (Syracuse, N.Y., Published by the author, 1853)
This sermon was preached at the ordination of Antoinette L. Brown, on 15 September 1853. Brown was one of the first women to be ordained in the Presbyterian church.
Lettered on cover: S.B. Anthony.
No. 13 in a collection of pamphlets lettered: Tracts and speeches on woman's rights.
Also available in digital form on the Library of Congress Web site.